Change points in marine recreational fisheries - the impact of stock status and fisheries regulations: A case from the western Baltic Sea - Lewin, Wolf-Christian; Weltersbach, Marc Simon; Haase, Kevin; Arlinghaus, Robert; Strehlow, Harry Vincent (Fisheries Research, 2023)
Marine recreational fisheries can be viewed as social-ecological systems in which sudden biological changes can affect interconnected social components. The Baltic Sea underwent various regime shifts, and the stock of western Baltic cod (Gadus morhua), a commercially and recreationally important target species, collapsed in 2016/17. This resulted in the first-time introduction of a bag limit in the recreational cod fishery. An eleven-year time series of recreational fisheries data was used to identify change points in the number of German cod anglers and in their catch and harvest rates, which may have occurred corresponding to the stock collapse. The number of anglers as well as their catch and harvest rates showed pronounced intra- and inter-annual fluctuations and the share of large cod in the catch decreased. Nonetheless, catch rates corresponded only weakly with cod stock biomass, suggesting that this fishery-related indicator was more responsive to the introduction of the bag limit than to the stock status. The study underlines the importance of long-term monitoring programs at appropriate spatial and temporal scales as a prerequisite for identifying change points in recreational fisheries and as an integral component of fisheries management to improve management in the future.